Economic Relationships Between Sub-Saharan Africa and China: An Alternative Theoretical and Policy Paradigm? - (:unkn) unknown (My University, 2021)
An emerging question in the literature on the relationship between China and Sub-Saharan Africa is as to whether Chinese engagements provide for developing economies an alternative paradigm to mainstream models of economic theories and policies, an example being the framework promoted by the international financial institutions (IFIs). China has indeed been analyzed as an original model of development that has shared many core elements with those having characterized the East Asian "developmental states"notably active state intervention (industrial policies), in contrast with the IFIs framework. Against this background, it is argued that the main domains of China-Sub-Saharan African economic relationships, trade, investment, development finance, generally do not illustrate the model of China as a developmental state, being mainly driven by market or development cooperation motives. In some dimensions, however, they illustrate China's specific developmental model.
Keywords: African Research